The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/or.2017.5504
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hepatoma activities of ethyl acetate extract from Ampelopsis sinica root

Abstract: Ampelopsis sinica root (ASR) is a known hepatoprotective folk traditional Chinese medicine. The anti‑hepatoma activity of ethyl acetate extract from A. sinica root (ASRE) in vitro and in vivo and its possible mechanism were explored. This study was designed to investigate cytotoxicity by MTT assay, induction of apoptosis via Hoechst 33258 staining, scanning electron microscopy and bivariate flow cytometric analysis (Annexin V-FITC/PI), inflammation and apoptosis related genes expression by RT-PCR and p53 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This species has been found in Anhui, Chongqing, Sichuan, Taiwan and other provinces in China [94] Notes: Ampelopsis sinica root (ASR) is a traditional Chinese medicine known to have a hepatoprotective function. Moreover, it has been proven having anti-hepatocellular carcinogenic activity and to inhibit Hepatitis B virus activity [95][96][97]. Our rust collection (GMB00110) on Ampelopsis sinica is compatible with Neophysopella ampelopsidis [98].…”
Section: Taxonomymentioning
confidence: 99%
“…This species has been found in Anhui, Chongqing, Sichuan, Taiwan and other provinces in China [94] Notes: Ampelopsis sinica root (ASR) is a traditional Chinese medicine known to have a hepatoprotective function. Moreover, it has been proven having anti-hepatocellular carcinogenic activity and to inhibit Hepatitis B virus activity [95][96][97]. Our rust collection (GMB00110) on Ampelopsis sinica is compatible with Neophysopella ampelopsidis [98].…”
Section: Taxonomymentioning
confidence: 99%
“…Following treatment, the relative viability (to vehicle control group) of the cells was detected according to the kit manufacturer's instructions. The relative cell viability was calculated using the following formula: relative cell viability (%) = (1 -(OD control -OD treated )/ OD control ) × 100% [16].…”
Section: Cell Viability Testmentioning
confidence: 99%
“…The findings showed that ASRE had prominent antihepatoma activity, which possibly involved the decreased regulation of inflammatory cytokines such as cyclooxygenase-2, 5-lipoxygenase and FLAP, augment of p53 protein expression and the ratio of bax/bcl-2, caspase-3 activation, as well as survivin repression. Moreover, ASR was found to be nontoxic on normal cells, suggesting that it may serve as a potential therapeutic agent for HCC treatment [55].…”
Section: Functional Roles Of Chinese Medicine Extracts and Fractions mentioning
confidence: 99%